Organizational Culture and Identity Unity and Division at Work - Parker, Martin; Parker, Martin (SAGE Publications, 1999)
Organizational Culture and Identity discusses the literature concerned with culture in organizations and explains why the term has been invoked with such enthusiasm. Martin Parker presents further ways of thinking about organizations and culture which suggest that organizational cultures should be seen as `fragmented unities' in which members identify themselves as collective at some times and divided at others.